Effects of circle of willis anatomic variations on angiographic and clinical outcomes of coiled anterior communicating artery aneurysms. - Tarulli, E; Sneade, M; Clarke, A; Molyneux, A; Fox, A (American Society of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Anterior communicating artery aneurysms account for one-fourth of all intracranial aneurysms and frequently occur in the context of A1 vessel asymmetry. The purpose of this study was to correlate circle of Willis anatomic variation association to angiographic and clinical outcomes of anterior communicating aneurysm coiling. MATERIALS AND METHODS: The Cerecyte Coil Trial provides a subgroup of 124 cases with anterior communicating artery aneurysms after endovascular coiling. One hundred seventeen of 124 anterior communicating artery aneurysms had complete imaging and follow-up for clinical outcome analysis, stability of aneurysm coil packing, and follow-up imaging between 5 and 7 months after treatment. Clinical outcomes were assessed by the mRS at 6 months. RESULTS: Anterior cerebral artery trunk-dominance was seen in 91 of 124 (73%) anterior communicating artery aneurysms and codominance in 33 of 124 (27%) anterior communicating artery aneurysms. There was no significant difference (P > .5) in treatment success at 5-7 months for anterior communicating artery aneurysms between the anterior cerebral artery trunk-dominant (49 of 86, 57%) and anterior cerebral artery trunk-codominant (19 of 31) groups. Angiographic follow-up demonstrates a statistically significant increase in neck remnants and progressive aneurysm sac filling with the A1 dominant configuration (n = 21, 24% at follow-up versus n = 11, 12% at immediate posttreatment, P = .035). There was no statistically significant difference in clinical outcomes between types of anterior cerebral artery trunk configuration (P > .5). CONCLUSIONS: Anterior communicating artery aneurysms with anterior cerebral artery trunk-dominant circle of Willis configurations show less angiographic stability at follow-up than those with anterior cerebral artery trunk-codominance similar to other "termination" type aneurysms. This supports the hypothesis that anterior cerebral artery trunk-dominant flow contributes to aneurysm formation, growth, and instability after coiling treatment.